High performance computing in science and engineering : third International Conference, HPCSE 2017, Karolinka, Czech Republic, May 22-25, 2017, Revised selected papers /: third International Conference, HPCSE 2017, Karolinka, Czech Republic, May 22-25, 2017, Revised selected papers. (2018) - Unknown
No abstract available